2012
DOI: 10.1245/s10434-012-2400-9
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Pelvic and Aortic Lymphadenectomy in Advanced Ovarian Cancer Patients at the Time of Interval Debulking Surgery: A Double-Institution Case–Control Study

Abstract: Lymphadenectomy at the time of IDS could be omitted, at least in high-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 22 publications
4
44
0
Order By: Relevance
“…This finding is concordant with other data suggesting that lymphadenectomy does not seem to play a role in OS [40,41,42]. In our study, owing to the lack of uniform recommendations concerning lymphadenectomy, over the whole period of the study, lymphadenectomy during IDS after NAC was left to the discretion of the surgeon [43,44,45]. …”
Section: Discussionsupporting
confidence: 91%
“…This finding is concordant with other data suggesting that lymphadenectomy does not seem to play a role in OS [40,41,42]. In our study, owing to the lack of uniform recommendations concerning lymphadenectomy, over the whole period of the study, lymphadenectomy during IDS after NAC was left to the discretion of the surgeon [43,44,45]. …”
Section: Discussionsupporting
confidence: 91%
“…The rate of grade I and II lower extremity lymphedema within 1 year after selective lymphadenectomy was significantly lower (6.2%) than that of systematic lymphadenectomy (33.1%) (p<0.001). The incidence of post-operative lymphocysts is 20%–30% 7. In the present study the overall incidence of lymphocysts was 6.2% vs 27.1%, with symptomatic lymphocysts occurring in 0 vs 5.9%, in Groups 1 and 2, respectively.…”
Section: Discussionsupporting
confidence: 40%
“…A case-control trial by Fagotti et al7 did not show any difference in progression-free survival or overall survival between selective or systematic lymphadenectomy groups during interval debulking surgery. The present study also demonstrated that there was no significant difference in lymph nodes metastasis between Groups 1 and 2 (p=0.43).…”
Section: Discussionmentioning
confidence: 89%
“…However, a critical appraisal is needed regarding the surgical approach after neoadjuvant therapy. In fact, a variety of procedures are currently proposed at this time, ranging from standard cytoreductive procedures to the removal of all previously infiltrated tissues, including lymph nodes 10. Moreover, approaches may differ, with preliminary results showing minimally invasive surgery to be as effective as laparotomy at the time of interval surgery in patients with adequate response to chemotherapy 11 12…”
Section: Introductionmentioning
confidence: 99%